Nursing workforce, education, and training challenges to implementing extracorporeal membrane oxygenation services in Australian intensive care units: A qualitative substudy. Issue 1 (January 2023) - Ross, Paul; Watterson, Jason; Fulcher, Bentley J.; Linke, Natalie J.; Nicholson, Angus J.; Ilic, Dragan; Hodgson, Carol L.
Abstract: Background: The use of extracorporeal membrane oxygenation (ECMO) is increasing in the management of critical care patients. ECMO service delivery requires an organisation-supported approach to ensure appropriate resources to deliver training, equipment, capacity, staffing, and the required model of care for quality care delivery. The aim of this nested substudy was to explore challenges specific to nursing staff in ECMO services in Australian intensive care units. Methods: This was a nested substudy within a qualitative study using semistructured focus group discussions conducted with 83 health professionals, which included 40 nurses. There were 14 focus groups across 14 ECMO centres participating in the binational ECMO (EXCEL) registry of Australia and New Zealand. An inductive thematic analysis focused on the nurse's experiences of the barriers and facilitators for nursing in providing an ECMO service. Results: Four themes emerged relating to the nurse's experience of implementing ECMO services: workforce requirements, workload demands, models of care, and level of experience. The complexity and intensity of caring for ECMO patients may need to be considered an additional factor in the burnout in critical care nurses. Current nursing ratios and responsibilities in critical care need to be considered, with the opportunity for the development of specialist advanced practitioner nursing roles. Conclusion: This study highlights the challenges for nursing in providing ECMO services in the intensive care setting. The complexity and intensity of ECMO is challenging and leads to concerns regarding burnout and workforce preparedness. New models of care need to be considered to mitigate the barriers for nursing identified across ECMO centres.